A duplex one-step recombinase aided PCR assay for the rapid and sensitive detection of the isoniazid resistance genes katG and inhA in Mycobacterium tuberculosis - Han, Zhiqiang; Ou, Xichao; Zhang, Ruiqing; Lv, Xiaona; Wang, Yuxin; Li, Hongyi; Shen, Xinxin; Ma, Xuejun; Tie, Yanqing (Frontiers in Microbiology, 2025)
ObjectivesDrug resistance in tuberculosis seriously affects the eradication of tuberculosis, and isoniazid resistance is the second most commonly observed drug resistance in patients with tuberculosis. Timely and accurate detection of isoniazid resistance is critical to the treatment of tuberculosis.MethodsA duplex one-step recombinase-aided PCR (DO-RAP) assay was developed for the rapid and sensitive detection of the katG Ser315Thr and inhA-15 (C-T) mutations in Mycobacterium tuberculosis, which are the most common isoniazid-resistant mutations. Quantitative recombinant plasmids were used to evaluate the sensitivity of DO-RAP, and 91 Mycobacterium tuberculosis strains with different genotypes, as well as 5 common respiratory tract bacteria, were used to evaluate the specificity of DO-RAP. A total of 78 sputum specimens were simultaneously detected using DO-RAP, quantitative PCR (qPCR) and sanger sequencing of nested PCR products. Sanger sequencing results were used as the standard to verify the clinical performance of DO-RAP.ResultsThe reaction time of DO-RAP was less than 1 h. The sensitivity of DO-RAP was 2 copies/reaction, which was 10 times higher than qPCR. The sensitivity of DO-RAP for detecting heterogenous resistance was 5%. There was no cross-reactivity between the isoniazid wild-type gene, drug-resistant mutant genes, and other common respiratory tract bacteria. Compared with Sanger sequencing, the sensitivity, specificity, PPV and NPV of DO-RAP were all 100%. There were 7 specimens with gray zone or negative qPCR results but positive DO-RAP test results.ConclusionThe DO-RAP can be adopted in ordinary qPCR equipment for the rapid, highly sensitive and specific detection of the isoniazid resistance genes of Mycobacterium tuberculosis.